MiRNA-10a-5p Alleviates Insulin Resistance and Maintains Diurnal Patterns of Triglycerides and Gut Microbiota in High-Fat Diet-Fed Mice. (17th August 2020) - Guo, Yawei; Zhu, Xiaohui; Zeng, Sha; He, Mingyi; Xing, Xiurong; Wang, Changyuan
Abstract : miRNA-10a is rhythmically expressed and regulates genes involved in lipid and glucose metabolism. However, the effects of miRNA-10a on obesity and glucose intolerance, as well as on the diurnal pattern of expression of circadian clock genes, remain unknown. We explored the effects of miRNA-10a-5p on insulin resistance and on the diurnal patterns of serum triglycerides and gut microbiota in high-fat diet- (HFD-) fed mice. The results showed that oral administration of miRNA-10a-5p significantly prevented body weight gain and improved glucose tolerance and insulin sensitivity in HFD-fed mice. Administration of miRNA-10a-5p also maintained the diurnal rhythm of Clock, Per2, and Cry1 expression, as well as serum glucose and triglyceride levels. Surprisingly, the diurnal oscillations of three genera of microbes, Oscillospira, Ruminococcus, and Lachnospiraceae, disrupted by HFD feeding, maintained by administration of miRNA-10a-5p. Moreover, a strong positive correlation was found between hepatic Clock expression and relative abundance of Lachnospiraceae, both in control mice (r = 0.877 ) and in mice administered miRNA-10a-5p (r = 0.853 ). Furthermore, we found that along with changes in Lachnospiraceae abundance, butyrate content in the feces maintained a diurnal rhythm after miRNA-10a-5p administration in HFD-fed mice. In conclusion, we suggest that miRNA-10a-5p may improve HFD-induced glucose intolerance and insulin resistance through the modulation of the diurnal rhythm of Lachnospiraceae and its metabolite butyrate. Therefore, miRNA-10a-5p may have preventative properties in subjects with metabolic disorders.